Uwagi o elementach "obcych" w uzbrojeniu w okresie rzymskim na ziemiach Polski - Horbacz, Tadeusz J. (Acta Universitatis Lodziensis. Folia Archaeologica, 1983)
As "foreign" elements the author regards weapons produced in the Roman or provincial Roman workshops as well as the closer or more distant immitations in form, construction details, stylistic features and so forth, reflecting a partial assimilation of foreign ideas on the local cultural background. In the light of former archaeological literature only comparatively few elements in the Roman period armament on the territory of Poland were regarded as “foreign" ones. This opinion has been partially revised in result of studies on the double-edged side-arms. The studies enabled one to distinguish the swords which were either evidently imported (for instance the damascene pieces bearing the inscriptions and figural incrustations) or were believed to be imported (swords of gladius type fuller swords and so on). Denoting an unequal value of classifying criteria, the author takes up an estimation of their usefulness for such purposes. This brings him to distinguish two groups of criteria: 1. directly and 2. indirectly useful ones. The paper concerns also the finds of fragments of the scabbard fittings in forms regarded in literature as the "Roman" (strap loops globular and crescent chapes, suspension rings and for strap). The “foreign” Influences upon the defensive armament may reveal in the finds of basses bronze shield scattered on the territory of Poland, Using the mail (lorica hamata) in the Roman period on the area in question appears a combined problem (finds from Witaszewice, province of Płock). Traces of the discoveries of other "foreign" elements of armament (for example the helmets, spear-heads, shields, dagger) met in archaeological literature are verified by the author. Most of the “foreign" elements in Barbarian armament appears at the turn of the early and late Roman period. In the 2nd half of 2nd century. A.D. certain areas of Barbaricum entered the zone of special imperial interest, and in result of that begun so much as the Marcoman Wars. It is evident also in other categories of archaeological sources. There is no need to overvalue the significance of those impulsions, at least when the Polish territory is concerned. In armament they are visible only on the swords and different kinds of fittings related to swords. The "Roman“ influences upon other categories of armament usе to be either almost invisible or unrecorded. New qualities were accepted by selection and concerned only those elements the Barbarian warrior was familiar with. That was closely related to the Barbarian tactics and the way of maintaining a war. The adaptation of "foreign" idea which was partly or entirely unuseful in the local circumstances would be nothing but aimless. In Barbaricum this process reflects its strictly local varieties, and in that context the territory of Poland takes quite peripherial shape. In the author’s opinion in most cases the armament of "foreign" ’features against the Barbarian background was probably some immitation of the "Homan" pieces (forms, sort of raw-material-for instance the shield bosses-and so forth) including often the native features. So, the imports are unnumerous. Present state of investigations of the Roman period armament on the territory of Poland leaves much to be desired. An urgent need to carry cut some broadly outlined comparative metallographic analysis is likely to emerge. The application of the sole formal criterion-typical for the former research comes short and is no more sufficient at present.